Association of Tissue-Specific DNA Methylation Alterations with α-Thalassemia Southeast Asian Deletion. (9th November 2017) - Pangeson, Tanapat; Sanguansermsri, Phanchana; Sanguansermsri, Torpong; Seeratanachot, Teerapat; Suwanakhon, Narutchala; Srikummool, Metawee; Kaewkong, Worasak; Mahingsa, Khwanruedee
In the wild-type allele, DNA methylation levels of 10 consecutive CpG sites adjacent to the upstream 5′-breakpoint of α-thalassemia Southeast Asian (SEA) deletion are not different between placenta and leukocytes. However, no previous study has reported the map of DNA methylation in the SEA allele. This report aims to show that the SEA mutation is associated with DNA methylation changes, resulting in differential methylation between placenta and leukocytes. Methylation-sensitive high-resolution analysis was used to compare DNA methylation among placenta, leukocytes, and unmethylated control DNA. The result indicates that the DNA methylation between placenta and leukocyte DNA is different and shows that the CpG status of both is not fully unmethylated. Mapping of individual CpG sites was performed by targeted bisulfite sequencing. The DNA methylation level of the 10 consecutive CpG sites was different between placenta and leukocyte DNA. When the 10th CpG of the mutation allele was considered as a hallmark for comparing DNA methylation level, it was totally different from the unmethylated 10th CpG of the wild-type allele. Finally, the distinct DNA methylation patterns between both DNA were extracted. In total, 24 patterns were found in leukocyte samples and 9 patterns were found in placenta samples. This report shows that the large deletion is associated with DNA methylation change. In further studies for clinical application, the distinct DNA methylation pattern might be a potential marker for detecting cell-free fetal DNA.